Orientozeuzera martinii sp. nov., a new species of Carpenter-Moths (Lepidoptera: Cossidae) from Borneo - Yakovlev, Roman V.; Witt, Thomas J. (Zootaxa, 2015)
Orientozeuzera martinii Yakovlev & Witt sp. nov. is described from Borneo Island (Trus Madi)